ANALISIS IMPLEMENTASI PROGRAM ASI EKSLUSIF DI DINAS KESEHATAN KABUPATEN TAPANULI SELATAN - Fahmi, Ismail; Siregar, Yenni Farida (Jurnal Kesehatan Ilmiah Indonesia (Indonesian Health Scientific Journal), 2018)
The low coverage of Exclusive breastfeeding is one of the health problems that must get more attention from the government, both the central government and the regional government. The coverage of Exclusive Breastfeeding in South Tapanuli Regency tended to decrease in 2013 by 34.58%, in 2014 which was 14.05%, in 2015 which was 22.2%. The resolution of the World Health Assembly (WHA) in 2001 confirmed that child growth optimal is one of the children’s rights. Implementation of programs to increase the use of breast milk is a priority because of the broad impact on nutritional status and health of children under five. The type of descriptive survey research with a qualitative approach The informants in this study were taken purposively, namely from the South Tapanuli District Health Office namely the Secretary of the Health Office, Nutrition Section Head, Nutrition Section Staff, Program Planning Sub-Section Head directly related to the Exclusive breastfeeding program. The results of health human resources research in the implementation of the exclusive breastfeeding program are nutrition section officers and have multiple assignments.